The helping interview - Benjamin, Alfred (Boston : Houghton Mifflin, 1981)
Conditions. Stages. Attitudes and behavior. Recording the interview. The question. Communication. Responses and leads.
Keywords: Counseling; Interviewing; Counseling; Interviewing; Helping behavior